The Programming Process / An Introduction Using Vdm and Pascal - Bush J. Vicky; Cottam D. Ian; Latham T. John (Addison-Wesley Publishing Company, 1990)
This book explains the process of software development, featuring formal specifications, at the introductory level. Preface, Introduction, Find the Average of Some Numbers, What is the Maximum Salary, Match - Snatch - A Variation on Nim, Telegraph Analysis, Time-Date Display Program, Interchangeable Parts System, Key Word in Context, Dynamic Data Types of KWIC, String Search - A Simple Software Tool, Specification of the String Package, Birds and Bees, Implementation of the Strings Package, Birds and Bees, Implementation of the Strings Package, Bibliography, Index.